Antimicrobial resistance profile of Escherichia coli isolated from raw chicken meat in a selected wet market in Manila City, Philippines - Dela Cruz, Angela Lorraine G.; Dimaapi, Lynder Kyle A.; Francisco, Roger Andrei D.; Noble, Rei Gilian D.; Sabangan, Hayley Emerald G.
Background: Antimicrobial resistance (AMR) is a leading global public health concern as it resulted in more difficult-to-treat infections and fatalities. In the Philippines, drug-resistant E. coli, including multidrug resistant (MDR), extended-spectrum beta-lactamase (ESBL)-producing, carbapenemase-producing carbapenem-resistant (CP-CR) E. coli, have been isolated from common food animals, increasing the risk of cross-contamination between humans, animals, and the environment. However, there is a lack of data on the distribution of E. coli in chicken meat in public wet markets. This study aims to describe the AMR profile of E. coli in raw chicken meat from retail stalls in a selected wet market in Manila City.